Preparative separation and purification of two highly polar alkaloids derived from Semen Strychni extracted with dichloromethane by high‐speed countercurrent chromatography. Issue 19 (October 2016) - Ma, Fengsen; Wu, Xiaojuan; Yu, Yan; Tong, Shengqiang; Liang, Yi; Fang, Jianqiao; Chen, Haibo
Abstract : Brucine chloromethochloride and strychnine chloromethochloride, the two chloromethochloride derivatives formed during the extraction of Semen Strychni in which dichloromethane was used as the extracting solvent, were isolated and purified by high‐speed countercurrent chromatography for the first time. The two‐phase solvent system composed of chloroform/methanol/0.3 mol/L hydrochloric acid (4:3:2, v/v/v) was selected for separation. From 300 mg of the crude extracts, 56.2 mg of brucine chloromethochloride and 60.2 mg of strychnine chloromethochloride were obtained with the purity of 99.78 and 96.99%, respectively, and the structures were confirmed by mass spectrometry, 1 H, 13 C, and two‐dimensional NMR spectroscopy. The results indicated that the present method is a powerful technology for large‐scale isolation of alkaloids from Semen Strychni .